Jimmy's Sunny Book - Dowling, Paul (Anderson Press Ltd, 1994)
An interactive book that celebrates the joys of a summer day. Jimmy and his puppy head outdoors on a sunny summer day. They swim in a pool and play with their shadows. With the reader's pull of the tab, magic happens--the sun comes up, shadows appear, Jimmy is drenched in water, and Puppy drinks from a bowl. Bright, colorful pictures and a simple, lively text make this a fun read.
Keywords: Juvenile literature-Fiction